Strategi Pengelolaan Sampah Berkelanjutan pada Industri Rokok Menggunakan Konsep 5R (Reduce, Reuse, Recycle, Recovery, and Repair) - Yuni Dwi Setyaningsih; Endang Hilmi; Roy Andreas; Edy Suyanto; Abdul Aziz Nasihuddin (School of Postgraduate Studies, Diponegoro Univer, 2023)
Industrial waste is considered to have a higher economic value. The cigarette industry is a large industry that involves thousands of workers, so it is necessary to carry out good waste/garbage management so as not to pollute the surrounding environment. The Ministry of National Development Planning/BAPPENAS in collaboration with United Nations Development Program (UNDP) and supported by the Government of Denmark, launched a new concept on the development of a Circular Economy in Indonesia. The circular economy encourages a business model oriented to Reduce, Reuse, Recycle, Recovery and Repair (5R). The implementation of 5R concept approach can reduce the consumption of new materials by up to 30% in 2035 and 50% in 2050. This study aims to find out how to implement a sustainable waste management strategy using the 5R concept in the Cigarette Industry. The data were collected by means of observation and interviews with cigarette factory PT. X, The Department of Housing and Settlements and Environment Kebumen Regency and academics. The method used is descriptive analysis quantitative, and Analytical Hierarchy Process (AHP). The results of this study show that during 2020, the average amount of waste generated in the cigarette factory of PT. X 1405.21 kg/month with the composition of waste in January 2021 consisting of 5.3% of category A waste; 5.5% category B; 51.3% category C; 1% category D; 36.5% category E; and 0.5% category F. Waste management in the cigarette factory of PT. X is broadly in accordance with Presidential Regulation No. 97 of 2017 regarding Indonesian National Strategy Policy on Managing Domestic Waste and Domestic Waste Equivalents. The suggested main alternative strategy is by using good/raw material in accordance with the procedure.